The role of urban green infrastructure in mitigating land surface temperature in Bobo-Dioulasso, Burkina Faso (2015)
Green infrastructure in developed countries has been used as a climate change adaptation strategy to lower increased temperatures in cities. But, the use of green infrastructure to provide ecosystem services and increase resilience is largely overlooked in climate change and urban policies in the developing world. This study analyzed the role of urbanization and green infrastructure on urban surface temperatures in Bobo-Dioulasso, Burkina Faso, in sub-Saharan Africa. We use available geospatial data and techniques to spatially and temporally explore urbanization and land surface temperatures (LSTs) over 20 years. The effect of specific green infrastructure areas in the city on LSTs was also analyzed. Results show increased urbanization rates and increased temperature trends across time and space. But, LST in green infrastructure areas was indeed lower than adjacent impervious, urbanized areas. Seasonal phenological differences due to rainfall patterns, available planting space, and site limitations should be accounted for to maximize temperature reduction benefits. We discuss an approach on how study findings and urban and peri-urban agriculture and forestry are being used for policy uptake and formulation in the field of climate change, food security, and urbanization by the municipal government in this city in Burkina Faso.